KOMITE AUDIT SEBAGAI PEMODERASI PENGARUH REPUTASI AUDITOR DAN TENURE AUDIT TERHADAP AUDIT REPORT LAG - Mariani, Komang; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aimed to examine the effect of auditor’s reputation, tenure audit, the audit committee, the interaction between the audit committee and the auditor's reputation as well as the interaction between the audit committee and audit tenure on audit report lag. Samples are 65 companies manufacturing in Indonesia Stock Exchange (BEI) 2012-2014 by purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that (1) auditor’s reputation negatively affect audit report lag, (2) tenure audit positive effect on audit report lag, (3) the audit committee does not affect the audit report lag, (4) the audit committee weaken the influence of auditor’s reputation on audit report lag, and (5) the audit committee weaken the influence of audit tenure on audit report lag
Keywords: auditor’s reputation, tenure audit, audit committees, audit report lag